Antiepileptic drugs and serotonin syndrome- A systematic review of case series and case reports. (October 2021) - Prakash, Sanjay; Rathore, Chaturbhuj; Rana, Kaushik; Patel, Harsh
Highlights: Cases of AED-induced SS have increased in the last decade. Valproate and lamotrigine are the two most common AEDs causing SS. Psychiatric disorders and migraine were the two most common primary disorders where patients developed SS. Several antiepileptic drugs have serotonergic properties and they increase serotonergic transmission. AED-induced SS is probably underreported in the literature as side effects profiles of various AED meet the criteria of SS. Abstract: Serotonin syndrome (SS) is a drug‑induced, potentially fatal, clinical syndrome resulting from drugs that have serotonergic properties. Several antiepileptic drugs (AEDs) are known to have serotonergic properties and it can be hypothesized that such AEDs can cause SS. This study aims to review the literature on SS in patients receiving AEDs. We performed a systematic review of Scopus and MEDLINE/PUBMED for case reports and case series of SS where patients had received at least one AED at the onset of symptoms. The cases published in the English literature between 1 January 1991 and 1 April 2021 were included. Initial search identified 1263 articles of which 63 (76 patients) were included in the final analysis. Most of the included cases (53 cases, 70%) have been published in the last 10 years. The mean age of the 76 patients was 40.6 ± 17.8 years, and 51% of cases were females. These patients had been exposed to a total of 8 different types of AEDs. Valproic acid was the most common drug (29, 38%), followed by lamotrigine (22, 29%), gabapentin (16, 21%), pregabalin (seven, 9%), topiramate (five, 7%) and carbamazepine (two, 3%). There has been one case each with phenytoin and oxcarbazepine. Seven (9%) patients received more than one AEDs. Most patients (67, 88%) also received other serotoninergic agents. Only nine (12%) patients were on AEDs alone. The most common clinical condition for using AEDs was psychiatric disorders (36 patients, 47.3%), followed by migraine (17, 22.4%), other painful conditions (15, 19.7%), epilepsy (7, 9.2%), and perioperative conditions (8, 10.5%). Death was reported in two patients. We suggest that AEDs, because of their serotonergic properties, may induce SS, especially in patients who are on another serotonergic agent.